Autoimmune swallowing disorders. Issue 6 (December 2016) - Amos, Janine; Baron, Anthony; Rubin, Adam D.
Abstract : Purpose of review: Dysphagia can be the presenting symptom of autoimmune disease. The otolaryngologist should be familiar with and consider these disorders when assessing the patient with swallowing difficulties. Recent findings: The present review gives a brief overview of Sjogren's syndrome, granulomatosis with polyangiitis, pemphigus and pemphigoid, rheumatoid arthritis, systemic lupus erythematosus, scleroderma and inflammatory myopathies, and how they affect swallowing. Diagnosis of these diseases is generally based off of clinical presentation, serology, and/or biopsy. Corticosteroids in combination with other immune modulators and symptomatic therapy are the mainstays of treatment. Treatment should be coordinated with a rheumatologist. Summary: The otolaryngologist should be able to recognize when a systemic disease may be the cause of a patient's dysphagia and guide appropriate evaluation. Furthermore, the otolaryngologist can help localize the specific nature of the swallowing problem and guide or provide treatment.